2010
DOI: 10.1111/j.1525-1314.2010.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Extending the applicability of the Raman carbonaceous‐material geothermometer using data from contact metamorphic rocks

Abstract: The degree of graphitization of carbonaceous material (CM) has been widely used as an indicator of metamorphic grade. Previous work has demonstrated that peak metamorphic temperature (T) of regional metamorphic rocks can be estimated by an area ratio (R2) of peaks recognized in Raman spectra of CM. The applicability of this method to low-pressure (<3 kbar) contact metamorphism was tested using Raman spectroscopic analyses of samples from two contact-metamorphic aureoles in Japan (Daimonji and Kasuga areas). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
387
2
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(426 citation statements)
references
References 53 publications
(168 reference statements)
25
387
2
12
Order By: Relevance
“…Furthermore, as CM does not undergo retrograde metamorphism, it is a useful proxy for the peak metamorphic grade or thermal alteration experienced by the host rock (e.g., Pasteris and Wopenka, 1991;Jehlicka and Bény, 1992;Wopenka and Pasteris, 1993;Marshall et al, 2001;Beyssac et al, 2002;Jehlicka et al, 2003;Aoya et al, 2010). Thus, comparison of the lineshape and spectral parameters (i.e., I D /I G ratio) of the Raman spectra of CM found within the Apex chert to that of CM from deposits of known metamorphic grade and thermal evolution allows for a semiquantitative elucidation of the thermal alteration history of the CM (but it does not allow for determination of an absolute temperature value).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as CM does not undergo retrograde metamorphism, it is a useful proxy for the peak metamorphic grade or thermal alteration experienced by the host rock (e.g., Pasteris and Wopenka, 1991;Jehlicka and Bény, 1992;Wopenka and Pasteris, 1993;Marshall et al, 2001;Beyssac et al, 2002;Jehlicka et al, 2003;Aoya et al, 2010). Thus, comparison of the lineshape and spectral parameters (i.e., I D /I G ratio) of the Raman spectra of CM found within the Apex chert to that of CM from deposits of known metamorphic grade and thermal evolution allows for a semiquantitative elucidation of the thermal alteration history of the CM (but it does not allow for determination of an absolute temperature value).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is attributed to a resonance enhancement effect of the D band (Pocsik et al, 1998). Recently, Aoya et al (2010) showed that there is little to no difference in I D /I G and A D /A G ratios for the same CM sample acquired from either excitation with a 514.5 or 532 nm laser. Therefore, it is valid to undertake a comparison of the above I D /I G ratios from the literature to delineate the thermal evolution of CM collected with either a 514.5 or 532 nm laser.…”
Section: Application Of Raman Microspectroscopy To Carbonaceous Materialsmentioning
confidence: 99%
“…Raman spectra of carbonaceous material (CM) consist of two board bands in the range of 1000-1800 cm -1 (first order region) and 2500-3100 cm -1 (second order region). The shape of the Raman spectra of CM show systematic changes due to its crystallinity (Beyssac et al 2002a, Rahl et al 2005, Aoya et al 2010, Lahfid et al 2010, especially within the first order Kouketsu (2014) defines the relation between the full width at half maximum (FWHM) of D1-band and the temperature of CM alteration.…”
Section: Products Of Hydrothermal Alterationmentioning
confidence: 99%
“…The average difference between the result of Equation 1 (Beyssac et al 2002) and Equation 2 (Rahl et al 2005) is about 25 °C. The temperature values for the graphitic carbonate phyllite (n=60) with the different calibrations are 368.1±15°C (Beyssac et al 2002), 384.2±38 °C (Rahl et al 2005) and 369.8±15 °C (Aoya et al 2010), while for the graphitic gneiss mylonite (n=55) they are higher, being 411.9±45 °C (Beyssac et al 2002), 387.5±35 °C (Rahl et al 2005) and 415.6±47 °C (Aoya et al 2010). The Student's t-test, the statistical probe regularly used to compare means of independent populations, confirms that at a 0.01 significance level the estimated metamorphic peak temperatures for the two units are different.…”
Section: á Nagy T M Tóth Central European Geology 55 2012mentioning
confidence: 99%
“…The process of graphitization has a strictly irreversible character; thus it primarily depends on the maximum temperature reached along a given P-T path (e.g. Beyssac et al 2002;Beyssac et al 2004;Wiederkehr et al 2011;Aoya et al 2010). Therefore the CM structure is insensitive to retrograde metamorphic overprint or polymetamorphic evolution (Wiederkehr et al 2011;Beyssac et al 2002;Wopenka and Pasteris 1993).…”
Section: Carbonaceous Materials Thermometer By Raman Microspectroscopymentioning
confidence: 99%